Exploration on Elderly Accessible Information Interaction Design Using Fuzzy Control - Peng, Hui (Journal of sensors, 2022)
With the increasing elderly population, the information intellectualization demand also rises substantially. At the same time, intelligent information interaction system- (IIIS-) controlled wheelchair’s automatic obstacle avoidance techniques have become extremely important in an intelligent social context. Therefore, this paper proposes an IIIS to help disabled groups and some older people enjoy the barrier-free information design and improve product information manipulation experience. Firstly, the functional requirements of the IIIS are analyzed, and the overall scheme of the IIIS is designed. Then, the control mode of IIIS is determined. Secondly, following research on the obstacle avoidance algorithm (OAA) based on fuzzy control, the obstacle avoidance control strategy is formulated for the elderly accessible wheelchair IIIS. Finally, experiments are designed to verify the control performance and simulate the automatic OAA of the designed IIIS. The experimental results indicate that the touch screen control system (TSCS) of mobile phone (MPHN) is more sensitive for the elderly accessible wheelchair control information system. By comparison, the joystick control system (JCS) is more straightforward to manipulate than the touch screen. The practicability of these two control methods is very strong. These two independent control methods meet the control performance requirements and improve the automatic obstacle avoidance performance of IIIS. The proposed IIIS based on TSCS and JSC can respond to input commands in real time, help the IIIS avoid obstacles, and acquire images, among other functions. Therefore, the proposed intelligent wheelchair design improves the interactive performance of the intelligent operating system, facilitates the travel of the elderly and the disabled, and has good practical value.